A Detailed Anatomy of Factor Misallocation in India - Duranton, Gilles; Ghani, Ejaz; Goswami, Arti Grover; Kerr, William (World Bank, Washington, DC, 2016)
This paper complements the results of earlier work on factor misallocation. The paper first expands the methodology and provides two important decompositions for the main indices. The main result is that factor and output misallocation across districts is at least as important as misallocation within districts. Second, the paper provides an exploration of the service sector that complements earlier work on manufacturing. The analysis shows that labor plays a fundamental role for misallocation in services, whereas land is the determining factor in manufacturing. Third, the paper expands our earlier work on the effects of policies on misallocation by looking at a much broader range of policies, and find strong evidence of their effects on misallocation. Finally, the paper take steps towards the identification of the causal effect of misallocation on output per worker by developing a novel instrumental variable approach and a simulation approach that allows for checking the consistency of the empirical results.